State of the Art and Future Applications of Industrial Wireless Sensor Networks - Ehrlich, Marco; Wisniewski, Lukasz; Jasperneite, Jürgen
In this paper an investigation of the State of the Art of Industrial Wireless Sensor Networks (IWSNs) is performed. Therefore the given industrial requirements, different wireless communication protocols, the defined basic architecture and open research questions will be analysed. Furthermore, current challenges from the research domain will be discussed and a real use case of IWSNs from a research project in cooperation with a local industrial partner will be evaluated. To conclude this paper an outlook of further developments and possible future applications of IWSNs will be sketched.